Folic acid supplementation and risk of colorectal neoplasia during long-term follow-up of a randomized clinical trial. Issue 4 (10th August 2019) - Passarelli, Michael N; Barry, Elizabeth L; Rees, Judy R; Mott, Leila A; Zhang, Dongyu; Ahnen, Dennis J; Bresalier, Robert S; Haile, Robert W; McKeown-Eyssen, Gail; Snover, Dale C; Cole, Bernard F; Baron, John A
ABSTRACT: Background: The Aspirin/Folate Polyp Prevention Study previously found folic acid increased risk of advanced and multiple colorectal adenomas during a surveillance colonoscopy interval starting about 3 y after randomization. Objective: We conducted secondary analyses to evaluate folic acid effects with additional follow-up after treatment was stopped. Methods: In total, 1021 participants recently diagnosed with colorectal adenomas were randomly assigned to 1 mg/d of folic acid ( n = 516) or placebo ( n = 505), with or without aspirin, beginning 6 July 1994. The original 3-y treatment period was extended into a subsequent colonoscopy interval, but eventually stopped prematurely on 1 October 2004. With additional post-treatment follow-up, a total of 663 participants who extended treatment completed a second colonoscopic surveillance interval after the initial 3-y follow-up. In addition, 490 participants provided information regarding a subsequent surveillance colonoscopy occurring before completion of follow-up on 31 May 2012, including 325 who had agreed to extended treatment. Study endpoints included conventional adenomas, sessile serrated adenomas/polyps (SSA/Ps), or colorectal cancer, and RRs with 95% CIs were adjusted for baseline characteristics associated with availability of follow-up. Results: Among those who extended treatment, any colorectal neoplasia was found in 118 (36%) participants assigned to placebo and 146 (43%) assigned to folic acid during the second surveillance interval (RR: 1.21; 95% CI: 0.99, 1.47; P = 0.06). Increased risk of SSA/P with extended folic acid supplementation was statistically significant during the second surveillance interval (RR: 1.94; 95% CI: 1.02, 3.68; P = 0.04). There was no evidence of post-treatment effects for any colorectal neoplasia (RR: 1.01; 95% CI: 0.80, 1.28; P = 0.94), and the post-treatment effect for SSA/P was no longer statistically significant (RR: 1.38; 95% CI: 0.59, 3.19; P = 0.46). Conclusions: Delayed treatment effects were not observed, but folic acid may increase SSA/P risk. This trial was registered at clinicaltrials.gov as NCT00272324.